In vitro generation of functional liver organoid-like structures using adult human cells - Ramachandran, Sarada Devi; Schirmer, Katharina; Ghafoory, Shahrouz; Wölfl, Stefan; Simon-Keller, Katja; Marx, Alexander; Ebert, Matthias; Breitkopf-Heinlein, Katja (PLOS ONE, 2015)
In this study we used differentiated adult human upcyte® cells for the in vitro generation of liver organoids. Upcyte® cells are genetically engineered cell strains derived from primary human cells by lenti-viral transduction of genes or gene combinations inducing transient proliferation capacity (upcyte® process). Proliferating upcyte® cells undergo a finite number of cell divisions, i.e., 20 to 40 population doublings, but upon withdrawal of proliferation stimulating factors, they regain most of the cell specific characteristics of primary cells. When a defined mixture of differentiated human upcyte® cells (hepatocytes, liver sinusoidal endothelial cells (LSECs) and mesenchymal stem cells (MSCs)) was cultured in vitro on a thick layer of Matrigel™, they self-organized to form liver organoid-like structures within 24 hours. When further cultured for 10 days in a bioreactor, these liver organoids show typical functional characteristics of liver parenchyma including activity of cytochromes P450, CYP3A4, CYP2B6 and CYP2C9 as well as mRNA expression of several marker genes and other enzymes. In summary, we hereby describe that 3D functional hepatic structures composed of primary human cell strains can be generated in vitro. They can be cultured for a prolonged period of time and are potentially useful ex vivo models to study liver functions.
Gesehen am 21.03.2018